Microbial Diversity of Bacteria Involved in Biomineralization Processes in Mine-Impacted Freshwaters - Paganin, Patrizia; Alisi, Chiara; Dore, Elisabetta; Fancello, Dario; Marras, Pier Andrea; Medas, Daniela; Montereali, Maria Rita; Naitza, Stefano; Rigonat, Nicola; Sprocati, Anna Rosa; Tasso, Flavia; Vacca, Salvatore; et al. (Frontiers in Microbiology, 2021)
In order to increase the knowledge about geo-bio interactions in extreme metal-polluted mine waters, we combined microbiological, mineralogical and geochemical analyses to study the indigenous sulphate-reducing bacteria involved in the heavy metal (HM) biomineralization processes occurring in Iglesiente and Arburese districts (SW Sardinia, Italy). Anaerobic cultures from sediments of two different mining-affected streams of this regional framework were enriched and analysed by 16S rRNA Next Generation Sequencing (NGS) technique, showing sequences closely related to sulphate-reducing bacteria (SRB) classified in taxa typical of environments with high concentrations of metals (Desulfovibrionaceae, Desulfosporosinus). Nevertheless, the most abundant genera found in our samples did not belong to the traditional SRB groups (i.e., Rahnella, Acinetobacter). The bio-precipitation process mediated by these selected cultures was assessed by anaerobic batch tests performed with polluted river water showing a dramatic (more than 97%) Zn decrease. Scanning electron microscopy (SEM) analysis revealed the occurrence of Zn sulphide with tubular morphology, suggesting a bacteria-mediated bio-precipitation. The inocula represent two distinct communities of microorganisms, each adapted to peculiar environmental conditions. However, both the communities were able of using pollutants in their metabolism and tolerating HMs by detoxification mechanisms. The Zn precipitation mediated by the different enriched cultures suggests that SRB inocula selected in this study have great potentialities for the development of biotechnological techniques to reduce contaminant dispersion and for metal recovery.